Evaluation of ecosystem service value based on land use change and analysis of driving forces in Ningxiang City, a representative county in the metropolitan hinterland in Hunan Province, China - Song, Zhen; Chen, Ming; Zhou, Huanzhan; Xiao, Yuexin; Wang, Tao; Shi, Zhao (Frontiers in Environmental Science, 2025)
The counties in the metropolitan hinterland, due to their unique locational advantages and pivotal functions, have emerged as crucial strategic pivots for economic development of cities. However, the rapid pace of urbanization has exerted considerable pressure on the ecosystems of these counties. Against this backdrop, assessing the ecosystem service value and its driving factors in these regions is of significant decision-making importance for promoting the coordinated development of urban economy and ecological conservation. Therefore, this study used the revised equivalent factor method to evaluate the spatial-temporal variation of regional ESV by the perspective of land use transformation in Ningxiang City during the years 2010, 2016 and 2022. The driving mechanism of ESV spatial differentiation was explored by combining geographic detector and geographically weighted regression (GWR) model. The results revealed that: (1) From 2010 to 2022, the area of construction land expanded the most, while the areas of ecological land such as forest land, water body and grassland decreased continuously. Accordingly, the total ESV declined consistently, dropping from 121.03 × 108 yuan to 113.93 × 108 yuan, with notable decreases of ESV in hydrological regulation services, forest land and water body. (2) At the grid unit and township (street) spatial scales, ESV demonstrated a northwest-high-northeast-low distribution pattern with significant spatial clustering effects, revealing persistent ecological degradation risks in the northeast. (3) Geographic detector revealed that synergistic effects of multiple natural and socio-economic driving factors shaped the spatial differentiation of the regional ESV. The main driving factors identified were the normalized vegetation index (NDVI), human impact index (HAI), and population density (POP). The influence of NDVI on ESV was generally higher in the west than east, while the negative influence intensity of HAI and POP on ESV gradually weakened from east to west. Based on the perspective of high-precision ESV assessment in small areas, this study provided scientific support for ecological policy formulation and sustainable land-use planning in Ningxiang City as well as similar counties.